A TBA approach to thermal transport in the XXZ Heisenberg model. (6th October 2017) - Zotos, X
Abstract: We show that the thermal Drude weight and magnetothermal coefficient of the 1D easy-plane Heisenberg model can be evaluated by an extension of the Bethe ansatz thermodynamics formulation by Takahashi and Suzuki (1972 Prog. Theor. Phys .48 2187). They have earlier been obtained by the quantum transfer matrix method (Klümper 1999 Z. Phys . B91 507). Furthermore, this approach can be applied to the study of the far-out of equilibrium energy current generated at the interface between two semi-infinite chains held at different temperatures.